Two-component condensation deacidification type silicone adhesive capable of being rapidly and deeply cured and preparation method

By introducing the synergistic catalytic effect of the condensation and deacidification reaction of silicone condensation and dehydration reactions of inorganic acid condensation and dehydration in silicone glue, the problem of difficulty in achieving rapid deep curing of existing silicone glues is solved, and rapid curing and efficient adhesiveness under room temperature conditions are achieved The effect of connection.

CN119490814AActive Publication Date: 2025-02-21WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311035367.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-21
Estimated Expiration
2043-08-17

AI Technical Summary

Technical Problem

The existing condensation silicone adhesives are difficult to achieve rapid deep curing at room temperature, limiting their use in rapid bonding positioning and sealing applications.

Method used

Rapid deep curing is achieved by introducing the synergistic catalytic effect of the condensation and deacidification reaction of silicone condensation and dehydration reaction in silicone glue. The adhesive includes component A and component B, which contains 107 silicone oil, filler and tungstate, and component B contains dimethyl silicone oil, filler, silicate, crosslinker and catalyst.

Benefits of technology

The curing depth of ≥30mm within 24 hours under room temperature conditions was achieved, which significantly improved the working efficiency, and the generated inorganic heteropolyate can be used as a tackifier to enhance the bonding effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004398759390000031
    Figure BDA0004398759390000031
  • Figure BDA0004398759390000041
    Figure BDA0004398759390000041
  • Figure BDA0004398759390000081
    Figure BDA0004398759390000081
Patent Text Reader

Abstract

The invention relates to a two-component condensation deacidification type silicone adhesive capable of being rapidly and deeply cured, and the two-component condensation deacidification type silicone adhesive is prepared from a component A and a component B. The component A is prepared from alpha, omega-dihydroxy polydimethylsiloxane, filler and tungstate; and the component B comprises dimethyl silicone oil, a filler, silicate, a cross-linking agent and a catalyst. In the curing process of the adhesive, the effect of concerted catalysis can be achieved through condensation, deacidification and vulcanization of organic silicon and condensation and dehydration reaction of inorganic heteropolyacid, rapid deep curing of the deacidification type organic silicon adhesive is finally achieved, and the curing depth of an adhesive layer in 24 h can be larger than or equal to 30 mm; and meanwhile, the formed silicon-tungsten heteropoly acid can also be used as an inorganic tackifier to improve the bonding effect of the organic silicon adhesive on a base material. The adhesive is suitable for application scenes which need to be rapidly cured and have good sealing and bonding requirements, and the working efficiency can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a two-component condensation deacidification type silicone adhesive capable of rapid and deep curing, belonging to the field of organic silicone sealants. Background Art

[0002] Organic silicone adhesive is widely used in construction, industry, aerospace, electronics, automobiles, new energy, photovoltaics and other fields because of its strong anti-aging ability, good weather resistance, excellent impact resistance, small shrinkage, excellent electrical properties and insulation ability.

[0003] Condensation type silicone adhesive is usually α, ω-dihydroxypolydimethylsiloxane (commonly known as 107 silicone oil) and a cross-linking agent that are vulcanized under the action of a catalyst. This process requires reaction with moisture in the air to form an elastomer. Depending on the selected cross-linking agent, condensation type silicone adhesive can be divided into deacidification type, deoxime type, dealcoholization type, deamine type, deamidation type and deketone type.

[0004] The curing effect of condensation silicone adhesive depends on the temperature, humidity and thickness of the adhesive layer. Under typical environmental conditions (temperature 25°C, humidity 50% RH), the adhesive layer can be surface-dried after 5 to 30 minutes, and the initial curing of the adhesive layer with a thickness of 0.1-2mm can be achieved within one day. However, as the curing depth increases, the speed at which the water required for the condensation reaction migrates from the surface to the inside will become slower and slower. It often takes more than a week to achieve a curing depth of more than 10mm and sufficient bonding strength to the substrate. This shortcoming makes it unable to meet the requirements of rapid bonding positioning and sealing, especially in application scenarios that emphasize production efficiency, such as home appliances, consumer electronics, etc., which will seriously affect the work efficiency of customers, thereby limiting the application and promotion of condensation silicone adhesives.

[0005] Therefore, it is very necessary to develop a condensation-type silicone adhesive that can be quickly cured at room temperature. The main idea of ​​patent CN201410296001.5 is to use low-viscosity hydroxy silicone oil to undergo an organic dehydration condensation reaction under the catalysis of organic tin to provide the moisture required for internal vulcanization of the silicone adhesive. However, in order to provide sufficient moisture, it is necessary to add more than 10,000 pppm of organic tin catalyst, and the heavy metal content exceeds the standard seriously; other patents that achieve rapid curing of silicone adhesive by introducing dehydration condensation reactions are rarely reported. Summary of the invention

[0006] In view of the fact that the current condensation-type silicone adhesive cannot achieve rapid deep curing, the present invention develops a fast curing two-component condensation deacidification silicone adhesive. During the curing process of the adhesive, the organic silicon condensation deacidification vulcanization and the inorganic acid condensation dehydration reaction can play a synergistic catalytic effect, and finally achieve rapid deep curing, which can achieve a curing depth of ≥30mm in 24 hours. The adhesive is suitable for application scenarios that require rapid curing and good sealing and bonding requirements, and can significantly improve work efficiency.

[0007] The present invention is achieved through the following technical solutions:

[0008] In the first aspect, the present invention provides a two-component condensation deacidification silicone adhesive that can be quickly and deeply cured:

[0009] A two-component condensation deacidification silicone adhesive capable of rapid deep curing comprises component A and component B, wherein:

[0010] Component A contains the following ingredients in weight percentage:

[0011] 107 Silicone oil 45-60%

[0012] Filler 25-40%

[0013] Tungstate 10-25%

[0014] Component B contains the following ingredients in weight percentage:

[0015]

[0016]

[0017] Preferably, the mass ratio of component A to component B is 4 to 10:1.

[0018] In the present invention, the 107 silicone oil is a base polymer, and the viscosity is preferably 500 to 50000 cP;

[0019] In the present invention, the filler is a compound of one or more of silicon micropowder, alumina, calcium carbonate, talcum powder, diatomaceous earth, and glass microbeads;

[0020] In the present invention, the tungstate is selected from one or more of ammonium tungstate, calcium tungstate, sodium tungstate, cobalt tungstate, cadmium tungstate, and ferrous tungstate, preferably calcium tungstate;

[0021] In the present invention, the dimethyl silicone oil is a plasticizer, and the viscosity is preferably 50-20000 cP;

[0022] In the present invention, the crosslinking agent is a combination of one or more of methyl triacetoxysilane, ethyl triacetoxysilane, propyl triacetoxysilane, di-tert-butoxy diacetoxysilane, and phenyl triacetoxysilane;

[0023] In the present invention, the silicate is selected from one or more of ammonium silicate, sodium silicate, potassium silicate and iron silicate, preferably ammonium silicate;

[0024] In the present invention, the catalyst is an organic tin catalyst, including one or more of monobutyltin oxide, dibutyltin oxide, dimethyltin oxide, dibutyltin acetate, dibutyltin dilaurate, diddecylthiodibutyltin, dibutyltin maleate and stannous octoate.

[0025] In the present invention, during the curing process of the adhesive, the small molecular acid X-COOH is released during the condensation deacidification and vulcanization of the organosilicon, which can be used as an acid regulator in the heteropolyacid formation process:

[0026]

[0027] Silicate and tungstate condense to form heteropolyacid tungstosilicoate [α-SiW 11 O 39 ] 8- The water released during the process can be used as an accelerator for the condensation, deacidification and vulcanization reaction of organic silicon:

[0028] 11[WO4] 2- +[SiO3] 2- +16H + →[α-SiW 11 O 39 ] 8- +8H2O

[0029] Through the synergistic catalytic effect of organic silicon condensation deacidification vulcanization and inorganic heteropoly acid condensation dehydration reaction, the effect of rapid deep curing was finally achieved; at the same time, the generated [α-SiW 11 O 39 ] 8- It can also be used as an inorganic thickener to enhance the bonding effect of silicone adhesives.

[0030] In a second aspect, the present invention provides a method for preparing the above-mentioned two-component condensation deacidification type silicone adhesive capable of rapid deep curing:

[0031] A method for preparing a two-component condensation deacidification silicone adhesive capable of rapid deep curing, the steps comprising:

[0032] (1) Add 107 silicone oil and filler into a stirring kettle, stir at a speed of 10-20 rpm / min, disperse at a speed of 300-500 rpm / min, heat to 100-130°C, keep warm, vacuum and stir for 1-3 hours, then cool to below 40°C, add tungstate, stir at a speed of 20-30 rpm / min, disperse at a speed of 800-1000 rpm / min, vacuum and stir for 10-20 minutes to obtain component A;

[0033] (2) Add dimethyl silicone oil, filler, silicate, crosslinking agent and catalyst into a stirred tank, stir at a speed of 10-20 rpm / min, disperse at a speed of 300-500 rpm / min, evacuate and mix thoroughly for 10-20 min to obtain component B;

[0034] The component A prepared in step (1) and the component B prepared in step (2) are respectively packaged into KIT packaging tubes and sealed for storage, thereby obtaining a two-component condensation deacidified silicone adhesive that can be rapidly and deeply cured.

[0035] The adhesive of the present invention is suitable for application scenarios that require rapid curing and good sealing and bonding requirements, and can significantly improve work efficiency.

[0036] The present invention has the following advantages and beneficial effects compared with the prior art:

[0037] During the curing process of the adhesive of the present invention, the condensation deacidification vulcanization reaction of the organic silicon and the condensation dehydration reaction of the inorganic acid can play a synergistic catalytic effect, and finally realize the rapid curing of the deacidified organic silicon adhesive, and can achieve the effect of a curing depth of ≥30mm in 24 hours; the curing process is carried out simultaneously from the surface and the inside, and is basically not affected by the environmental humidity;

[0038] The [α-SiW 11 O 39 ] 8- It can also be used as an inorganic thickener to enhance the bonding effect of silicone adhesives.

[0039] This adhesive has good application prospects in scenarios that focus on production efficiency, such as home appliances, consumer electronics and other fields. DETAILED DESCRIPTION

[0040] For ease of understanding of the present invention, preferred embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. The examples cited are only used to explain the present invention and are not used to limit the scope of the present invention.

[0041] Example 1

[0042] 5690g of 5000cp 107 silicone oil and 3240g of silicon powder were added into a double planetary stirring kettle, the stirring speed was 15rpm / min, the dispersion speed was 500rpm / min, heated to 120℃, kept warm, vacuumed and stirred for 2h, then cooled to below 40℃, 1070g of calcium tungstate was added, the stirring speed was 20rpm / min, the dispersion speed was 800rpm / min, vacuumed and stirred for 10min to obtain component A;

[0043] 357 g of 1000 cP dimethyl silicone oil, 418.2 g of silicon powder, 133.8 g of ammonium silicate, 89 g of methyltriacetoxysilane and 2 g of dibutyltin dilaurate were added into a double planetary stirring kettle, the stirring speed was 15 rpm / min, the dispersion speed was 500 rpm / min, and the mixture was thoroughly mixed and stirred for 20 min to obtain component B;

[0044] The A component and the B component are respectively packed into a 10:1 KIT packaging tube and sealed for storage to obtain Example Sample 1.

[0045] Example 2

[0046] 5690g of 1500cp 107 silicone oil and 2740g of calcium carbonate were added into a double planetary stirring kettle, the stirring speed was 15rpm / min, the dispersion speed was 500rpm / min, heated to 120℃, kept warm, vacuumed and stirred for 2h, then cooled to below 40℃, 1570g of sodium tungstate was added, the stirring speed was 20rpm / min, the dispersion speed was 800rpm / min, vacuumed and stirred for 10min to obtain component A;

[0047] 377 g of 100 cP dimethyl silicone oil, 368.5 g of calcium carbonate, 183.5 g of sodium silicate, 68 g of ethyl triacetoxysilane and 3 g of dibutyltin maleate were added into a double planetary stirring kettle at a stirring speed of 15 rpm / min and a dispersion speed of 500 rpm / min, and the mixture was thoroughly mixed and stirred for 20 min under vacuum to obtain component B;

[0048] The A component and the B component are respectively packed into 10:1 KIT packaging tubes and sealed for storage to obtain Example Sample 2.

[0049] Example 3

[0050] 4690g of 10000cp 107 silicone oil and 3240g of alumina powder were added into a double planetary stirring kettle, the stirring speed was 15rpm / min, the dispersion speed was 500rpm / min, heated to 120℃, kept warm, vacuumed and stirred for 2h, then cooled to below 40℃, 2070g of ammonium tungstate was added, the stirring speed was 20rpm / min, the dispersion speed was 800rpm / min, vacuumed and stirred for 10min to obtain component A;

[0051] 307 g of 5000 cP dimethyl silicone oil, 348.6 g of alumina powder, 233.4 g of ammonium silicate, 107 g of phenyltriacetoxysilane and 4 g of dibutyltin maleate were added into a double planetary stirring kettle at a stirring speed of 15 rpm / min and a dispersion speed of 500 rpm / min, and the mixture was thoroughly mixed and stirred for 20 min to obtain component B;

[0052] The A component and the B component were respectively packed into 10:1 KIT packaging tubes and sealed for storage to obtain Example Sample 3.

[0053] Example 4

[0054] 4950g of 10000cp 107 silicone oil and 2840g of alumina powder were added into a double planetary stirring kettle, the stirring speed was 15rpm / min, the dispersion speed was 500rpm / min, heated to 120℃, kept warm, vacuumed and stirred for 2h, then cooled to below 40℃, 2210g of ammonium tungstate was added, the stirring speed was 20rpm / min, the dispersion speed was 800rpm / min, vacuumed and stirred for 10min to obtain component A;

[0055] 307 g of 3000 cP dimethyl silicone oil, 394 g of alumina powder, 197 g of ammonium silicate, 100 g of phenyltriacetoxysilane and 2 g of dibutyltin dilaurate were added into a double planetary stirring kettle, the stirring speed was 15 rpm / min, the dispersion speed was 500 rpm / min, and the mixture was thoroughly mixed and stirred for 20 min under vacuum to obtain component B;

[0056] Component A and component B were separately packed into 6:1 KIT packaging tubes and sealed for storage to obtain Example Sample 4.

[0057] Comparative Example 1

[0058] 5690g of 5000cp 107 silicone oil and 4310g of silicon powder were added into a double planetary stirring kettle, the stirring speed was 15rpm / min, the dispersion speed was 500rpm / min, the mixture was heated to 120℃, vacuum stirred for 2h, and then cooled to room temperature to obtain component A;

[0059] 357 g of 1000 cP dimethyl silicone oil, 552 g of silicon powder, 89 g of methyl triacetoxysilane and 2 g of dibutyltin dilaurate were added into a double planetary stirring kettle at a stirring speed of 15 rpm / min and a dispersion speed of 500 rpm / min, and the mixture was thoroughly mixed and stirred for 20 min under vacuum to obtain component B;

[0060] The A component and the B component were respectively packed into 10:1 KIT packaging tubes and sealed for storage to obtain comparative sample 1.

[0061] The above examples and comparative examples were placed under the same temperature and humidity (temperature 25±2°C, humidity 50±5%RH), and the curing depth (total adhesive layer height 40mm) at different time periods at room temperature was tested. At the same time, the shear strength of the samples to PC was tested at different time periods. The relevant comparison results are as follows:

[0062] Curing depth test method: After mixing the A / B components, pour them into a disposable plastic cup, control the glue layer thickness to 40mm, place the sample under a standard environment (temperature 25±2℃, humidity 50±5%RH), and take out the cured glue layer thickness for testing at different time periods.

[0063] Shear strength test method: GB T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material) standard.

[0064] Table 1 Comparison of curing depth of two-component deacidified silicone adhesive

[0065]

[0066] Table 2 Comparison of bonding strength of two-component deacidified silicone adhesive PC

[0067]

[0068] From the comparison of the performance data of the above embodiments and comparative silicone adhesives: the deep curing speed of embodiments 1, 2, 3, and 4 is significantly faster than that of comparative example 1 in which the inorganic heteropoly acid condensation dehydration reaction is not introduced. Embodiments 1, 2, 3, and 4 can reach a maximum curing depth of the adhesive layer of ≥30 mm after 24 hours; at the same time, compared with the bonding effect on PC material, embodiments 1, 2, 3, and 4 can achieve very high bonding strength in a short time compared with comparative example 1, and can reach the final bonding strength in 24 hours; the above proves that the condensation deacidification type silicone adhesive has the effects of rapid deep curing, rapid positioning, and sealing.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A two-component condensation deacidification silicone adhesive capable of rapid deep curing, characterized in that: Including component A and component B: Component A contains the following ingredients in weight percentage: 107 Silicone oil 45-60% Filler 25-40% Tungstate 10-25% Component B contains the following ingredients in weight percentage: Preferably, the mass ratio of component A to component B is 4 to 10:

1.

2. The silicone adhesive according to claim 1, wherein The viscosity of the 107 silicone oil is 500-50000 cP.

3. The silicone adhesive according to claim 1 or 2, wherein: The filler is one or more of silicon micropowder, aluminum oxide, calcium carbonate, talcum powder, diatomaceous earth, and glass microbeads.

4. The silicone adhesive according to any one of claims 1 to 3, wherein: The tungstate is selected from one or more of ammonium tungstate, calcium tungstate, sodium tungstate, cobalt tungstate, cadmium tungstate, and ferrous tungstate.

5. The silicone adhesive according to any one of claims 1 to 4, wherein: The dimethyl silicone oil has a viscosity of 50-20000 cP.

6. The silicone adhesive according to any one of claims 1 to 5, wherein: The silicate is selected from one or more of ammonium silicate, sodium silicate, potassium silicate and iron silicate.

7. The silicone adhesive according to any one of claims 1 to 6, wherein: The crosslinking agent is one or more of methyl triacetoxysilane, ethyl triacetoxysilane, propyl triacetoxysilane, di-tert-butoxy diacetoxysilane, and phenyl triacetoxysilane.

8. The silicone adhesive according to any one of claims 1 to 7, wherein: The catalyst is an organic tin catalyst, preferably one or more of monobutyltin oxide, dibutyltin oxide, dimethyltin oxide, dibutyltin acetate, dibutyltin dilaurate, diddecylthiodibutyltin, dibutyltin maleate, and stannous octoate.

9. The method for preparing the silicone adhesive according to any one of claims 1 to 8, comprising: (1) Add 107 silicone oil and filler into a stirring kettle, heat to 100-130°C, keep warm, evacuate and stir, then cool to below 40°C, add tungstate, evacuate and stir to obtain component A; (2) Add dimethyl silicone oil, filler, silicate, crosslinking agent and catalyst into a stirring kettle, and stir. Vacuum and mix thoroughly to obtain component B.

Citation Information

Patent Citations

  • High-transparency high-deep-layer-curing-speed double-component condensed organic silicon potting adhesive

    CN104017536A

  • Rapid curing type organosilicone sealant

    CN110205084A

  • Bi-component quick-curing organosilicon structural adhesive and preparation method thereof

    CN111057517A

  • High-temperature-resistant single-component silicone pouring sealant and preparation method thereof

    CN112266733A

  • Organic-inorganic hybrid heteropolyacid solid tackifier, preparation method and dealcoholized silicone adhesive

    CN115403517A